2013
DOI: 10.1007/s12672-013-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

SGTA: A New Player in the Molecular Co-Chaperone Game

Abstract: Small glutamine-rich tetratricopeptide repeat-containing protein α (SGTA) is a steroid receptor molecular co-chaperone that may substantially influence hormone action and, consequently, hormone-mediated carcinogenesis. To date, published studies describe SGTA as a protein that is potentially critical in a range of biological processes, including viral infection, cell division, mitosis, and cell cycle checkpoint activation. SGTA interacts with the molecular chaperones, heat shock protein 70 (HSP70) and HSP90, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 104 publications
0
44
0
1
Order By: Relevance
“…Upon androgen binding, SGTA is exchanged by another TPR containing protein such as the 52 kDa FK506 binding protein (FKBP52), an essential step for AR nuclear shuttling (17, 27, 28). It has been previously shown that the N-terminal region of SGTA (residues 21–40) is important for interaction with the AR hinge region (residues 630–645) (17, 29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon androgen binding, SGTA is exchanged by another TPR containing protein such as the 52 kDa FK506 binding protein (FKBP52), an essential step for AR nuclear shuttling (17, 27, 28). It has been previously shown that the N-terminal region of SGTA (residues 21–40) is important for interaction with the AR hinge region (residues 630–645) (17, 29).…”
Section: Resultsmentioning
confidence: 99%
“…Since the BF3 pocket is considered a co-chaperone binding site and is at the boundary with the hinge region, we suspected that a similar motif could exist in the SGTA protein, a co-chaperone that interacts with the AR hinge and plays a role in receptor cytoplasmic regulation (28, 29). Indeed, analysis of the SGTA protein sequence has identified a P A RT P P motif (residues 78–83) that had the potential to be recognized by the BF3 site.…”
Section: Discussionmentioning
confidence: 99%
“…6). Philp et al (42) proposed that SGTA may have a more predominant role in early receptor folding events mediated by Hsp70. Buchanan et al (16) demonstrated that SGTA overexpression inhibits hormone-induced translocation of the androgen receptor to the nucleus and propose a model in which SGTA acts to retain the receptor in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Small glutamine-rich tetratricopeptide repeat-containing protein-α (SGTA) is linked to several cellular processes including cell division, mitosis, cell cycle checkpoint activation, and viral infection. SGTA interacts directly with Hsp70 and may interact with Hsp90 via its TPR domain to facilitate maturation of the growth hormone and androgen receptors [42]. It has also been proposed that SGTA participates in the sequestration of client proteins in an inactive state.…”
Section: Introductionmentioning
confidence: 99%